An Allosteric Mechanism of Rho-dependent Transcription Termination - Epshtein, Vitaly (2010)
Rho is the essential RNA helicase that sets the borders between transcription units and adjusts transcriptional yield to translational needs in bacteria1–3. Although Rho is the first termination factor to be discovered4, the actual mechanism by which it reaches and disrupts the elongation complex (EC) is unknown. Here we show that the termination-committed Rho molecule associates with RNA polymerase (RNAP) throughout the transcription cycle, i.e. it does not require the nascent transcript for initial binding. Moreover, the formation of the RNAP-Rho complex is crucial for termination. We show further that Rho-dependent termination is a two-step process that involves rapid EC inactivation (trap) and a relatively slow dissociation. Inactivation is the critical rate-limiting step that establishes the position of the termination site. The trap mechanism depends on the allosterically-induced rearrangement of the RNAP catalytic center via the evolutionary conserved mobile trigger loop (TL) domain, which is also required for EC dissociation. The key structural/functional similarities, which we found between Rho-dependent and intrinsic (Rho-independent) termination pathways, argue that the allosteric mechanism of termination is general and likely to be preserved for all cellular RNAPs throughout evolution.